The Process of Implementing Divorce Cases in North Sumatra Religious Court after the Entry into force of PERMA Number 1 of 2016 - Rusli Halil Nasution; Asmuni Asmuni; Pagar Hsb (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The aims of the study are to find out the process of implementing divorce case in North Sumatera. This study is a qualitative and normative study of PERMA Number 1 of 2016 with its application in the North Sumatra Religious Court as a legal product in the present aspects that applies in testing the success of the regulation being implemented in the North Sumatra Court, especially in (three) 3 big cities namely the Court Medan, Binjai and Tebing Tinggi religion. The result shows that The implementation of peace in divorce cases in the North Sumatra Religious Court is not significant. In the implementation of divorce case mediation in the North Sumatra Religious Court, many factors influence, among others, technical and non-technical factors. The technical factor is the limitations of the Mediator, namely the absence of a list of non-Judge Mediators here will further aggravate the work of the Judge because of his work being double that is as a Panel Judge and Mediator Judge. So that the work of the Judge mediator is very ineffective and so is the non-judge mediator who must have an official certificate from the Supreme Court so that the training costs are large and the costs of the mediator are not protected by the Regulation